2021
DOI: 10.1007/s11356-021-13546-w
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and ecological responses to hydrological changes in benthic algal assemblages in a regulated river: application of algal metrics and multivariate techniques in river management

Abstract: The flow regime of the Wimmera River was substantially modified due to the construction of a water supply reservoir. Samples of diatoms, soft algae and measurements of water quality were analysed at ten sampling sites for three years (between February 2012 and November 2014) along the MacKenzie River, a tributary of the Wimmera River, in different seasons and under different flow regimes, to understand the spatial and temporal variation in the relationship between algal communities, water quality and stream co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Several authors have also reported similar observations in the river Ganga and other aquatic systems (Dwivedi & Srivastava, 2017 ; Gogoi et al, 2019 ; Kumar et al, 2015a , b 2017 , 2020 ; Matta et al, 2018 ; Sharma et al, 2016 ; Vajravelu et al, 2018 ; Wassie & Melese, 2017 ). Bacillariophyta, Charophyta, and Chlorophyta were assembled ubiquitously and were suggested to be bearable to high flow and sustained in comparable clean water (Atazadeh et al, 2021 ). Bacillariophyta was the dominant group in the present study, and several researchers also reported similar remarks on the river Ganga, which is consistent with our findings (Khanna et al, 2012 ; Kumar et al, 2022a , b ; Shukla et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have also reported similar observations in the river Ganga and other aquatic systems (Dwivedi & Srivastava, 2017 ; Gogoi et al, 2019 ; Kumar et al, 2015a , b 2017 , 2020 ; Matta et al, 2018 ; Sharma et al, 2016 ; Vajravelu et al, 2018 ; Wassie & Melese, 2017 ). Bacillariophyta, Charophyta, and Chlorophyta were assembled ubiquitously and were suggested to be bearable to high flow and sustained in comparable clean water (Atazadeh et al, 2021 ). Bacillariophyta was the dominant group in the present study, and several researchers also reported similar remarks on the river Ganga, which is consistent with our findings (Khanna et al, 2012 ; Kumar et al, 2022a , b ; Shukla et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The low abundance and diversity of phytoplankton in the monsoon season in the current study might be due to the high flow of water current, and only well-adapted phytoplankton species ( Cyclotell sp., Navicula sp., Synedra sp.) showed their presence (Inyang & Wang, 2020 ; Atazadeh et al, 2021 ). High diversity in the post-monsoon season might occur due to high phosphate in water.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms also play important roles in biotechnology, engineering, biology, and material science [321] but their main role in the general riverine environmental condition [29,322,323], water quality ecological assessment of aquatic systems [107,152,[324][325][326][327][328], eutrophication [78, 314,329], pollution [330,331], bioassessment [107,116,[332][333][334], and urbanization [335][336][337][338].…”
Section: Algae In the Role Of Indicators In The Assessment Of Stream ...mentioning
confidence: 99%
“…This is because it is essential to demonstrate the effect of pollutants on biota as the effect on water quality is also influenced by the nature of the receiving waters. Water in rivers can be classified, based on biology, hydrology, and quality, into different ecological categories of conditions such as bad, poor, moderate, good, or high [1][2][3]. Water pollution can be defined as the contamination of water bodies by the entrance of large amounts of materials/substances into those bodies, resulting in physical or chemical changes to the water, modifying the natural features of the water, degrading the water quality, and adversely affecting humans and the environment [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Water in rivers can be classified, based on biology, hydrology, and quality, into different ecological categories of conditions such as bad, poor, moderate, good, or high [1][2][3]. Water pollution can be defined as the contamination of water bodies by the entrance of large amounts of materials/substances into those bodies, resulting in physical or chemical changes to the water, modifying the natural features of the water, degrading the water quality, and adversely affecting humans and the environment [1,2]. Water pollution is a phenomenon in which the chemical, physical, and biological quality of natural waters is harmfully affected by the discharge of waste materials such as sanitary sewage [2,3], urban runoff [4], industrial waste [5], agricultural waste [6], animal husbandry effluents [7], vehicle-and traffic-related organic pollutants [8], and other industrial, urban, and agricultural waste materials [9].…”
Section: Introductionmentioning
confidence: 99%